Language Policy in Indonesian Elementary Schools: Balancing National, Local, And Foreign Languages - Matatula, Marles Yohannis; Tupalessy, Pricilia (Program Studi Pendidikan Bahasa Inggris FKIP, Universitas Pattimura Ambon, 2025)
With its linguistic diversity, Indonesia faces unique challenges in implementing an effective language policy in basic education. With more than 700 regional languages and a commitment to national unity, cultural preservation, and global competitiveness, the country's language policy seeks to balance the roles of Bahasa Indonesia, regional languages, and foreign languages, mainly English. A qualitative literature review approach was used to analyze existing scholarly works, policy documents, and government reports. This method identifies patterns in language policy implementation and common challenges schools face. It also examines the successes and failures of language policies in promoting national unity, cultural preservation, and global competitiveness. A comprehensive multilingual approach is recommended, integrating local languages in early childhood education, using Bahasa Indonesia as the primary language of instruction, and gradually introducing foreign languages. The study advocates for curricula tailored to local needs, better teacher training, and equitable distribution of resources to address gaps. This approach is critical to ensuring the sustainability of Indonesia's linguistic diversity, preserving cultural heritage, strengthening national identity, and improving students' global readiness.